TANTANGAN DAN PELUANG DIGITAL PEMASARAN BANK SYARIAH DI ASIA TENGGARA - riky kurniawan; muhamammad iqbal fasa (Cipta Kind Publisher, 2024)
The development of digital technology has significantly changed the landscape of the banking industry, including sharia banking in Southeast Asia. This research aims to identify the challenges and opportunities faced by Islamic banks in implementing digital marketing strategies. Through a comprehensive literature study, this research will analyze various factors that influence the success of Islamic bank digital marketing, such as regulations, competition, consumer behavior and technology adoption. It is hoped that the research results can contribute to the development of more effective digital marketing strategies for Islamic banks in the Southeast Asia region.